The Effect of Insiders and Work Discipline on Employee Performance with Transformational Leadership as a Moderating Variable According to Islamic Business Perspective : Study on Nuju Coffee Employees in Bandar Lampung - Eci Meiliyani; Ahmad Habibi; Yeni Susanti (CV. Publikasi Indonesia, 2024)
This research aims to examine the effect of Insiders and Work Discipline on Employee Performance with Transformational Leadership as a moderating variable in an Islamic business perspective. The object of research is Nuju Coffee employees in Bandar Lampung, totaling 105 people. Data were obtained through questionnaires and interviews, then analyzed using validity, reliability, and hypothesis testing with the SmartPLS application. The results showed that Insiders and Work Discipline have a significant influence on Employee Performance. In addition, Transformational Leadership is proven to moderate the relationship between Insiders and Work Discipline on Employee Performance. This research enriches the literature related to human resource management in the context of Islamic business and provides practical recommendations for companies in improving employee performance through an effective leadership approach and the implementation of good work discipline.